2013
DOI: 10.1039/c3nr00580a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent and colorimetric magnetic microspheres as nanosensors for Hg2+ in aqueous solution prepared by a sol–gel grafting reaction and host–guest interaction

Abstract: Fluorescent sensing TSRh6G-β-cyclodextrin fluorophore/adamantane-modified inclusion complex magnetic nanoparticles (TFIC MNPs) have been synthesized via the cooperation of a host-guest interaction and sol-gel grafting reaction. Powder X-ray diffraction, transmission electron microscopy, Fourier transform infrared spectroscopy, and UV-visible absorption and emission spectroscopy have been employed to characterize the material. Fluorescence and UV-visible spectra have shown that the resultant multifunctional nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…Additionally, the C-N and N-Cl characteristic peak appeared at around 1230 and 750 cmG 1 , respectively . The multiplet of C-O-C stretching is detected within the range of 1070-1170 cmG 1 regarding to the ether bond from ATMP units in polymers (Wang et al, 2013b). The presence of C-N, C-O-C and N-Cl vibration can act as marker for the formation of the ATMP structural units in polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the C-N and N-Cl characteristic peak appeared at around 1230 and 750 cmG 1 , respectively . The multiplet of C-O-C stretching is detected within the range of 1070-1170 cmG 1 regarding to the ether bond from ATMP units in polymers (Wang et al, 2013b). The presence of C-N, C-O-C and N-Cl vibration can act as marker for the formation of the ATMP structural units in polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…However, after forming the inclusion of adamantine in a β-CD cavity for PPV@MSN@PGMA@CD@ AD-SRhB after host-guest interactions, the probe can detect Hg 2+ from other interfering ions effectively. It has been reported that the metal ions such as Fe 3+ , Al 3+ and Hg 2+ can all induce ring-opening AD-SRhB [37][38][39] before the recognition between β-CD and AD-SRhB. In our work, Fe 3+ and Al 3+ hardly induce ring-opening AD-SRhB for the probe of PPV@MSN@PGMA@CD@ AD-SRhB after the host-guest recognition possibly due to the other stronger adsorption sites for Fe 3+ and Al 3+ presented in PPV@MSN@PGMA@CD nanoparticles.…”
Section: Selectivity Investigationmentioning
confidence: 99%
“…Ai et al described a novel optical biosensor for amantadine determination based on fluorescence resonance energy transfer (FRET) [36]. Wang et al have designed and fabricated the magnetic nanoparticle-based chemosensors for the detection of Hg 2+ , in which the rhodamine-cyclodextrin fluorophore moiety is loaded on the adamantane-functionalized magnetic silica microspheres surface via host-guest interactions [37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of metal selective sensors have been developed based on rhodamine derivatives with different recognize groups [17,18]. Li [19] and Duan [20] groups synthesized chemosensors for Hg 2?…”
Section: Introductionmentioning
confidence: 99%
“…This property makes b-CD to form supramolecular inclusion complexes with size suitable and hydrophobic small molecules, for example, adamantyl (AD) [17,25], azobenzene [26], nitrobenzene [27], and so on [28].…”
Section: Introductionmentioning
confidence: 99%